See it again, say it again : the artist as researcher - Wesseling, Janneke (Amsterdam : Valiz, 2011)
This publication "sheds light on the phenomenon of research in the visual arts. In 'artistic research,' practical acts (the making) and theoretical reflection (the thinking) go hand in hand, in a manner similar to creating and thinking being inextricably linked with artistic practice. -- This volume has been written from the perspective of art as practice. The majority of the authors are artists, while several artists provided visual contributions that elucidate the phenomenon of research in art. There are also contributions form theoreticians, who analyse how artistic research works (and how it is productive)"--P.[3] of cover.
The use and abuse of research for art and vice versa / Jeremiah Day -- Art research / Hilde Van Gelder -- Visual contribution / Aernout Mik -- Absinthe and floating tables / Frank Mandersloot -- The chimera of method / Jeroen Boomgaard -- Reform and education / Ruchama Noorda -- The artist as researcher : new roles for new realities / Graeme Sullivan -- Visual contribution / Aglaia Konrad -- Some thoughts on artistic research / Lonnie van Brummelen & Siebren de Haan -- Surface research / Henri Jacobs -- The artist's toolbox / Irene Fortuyn -- Knight's move : the idiosyncracies of artistic research / Kitty Zijlmans -- In leaving the shelter / Italo Zuffi -- Letter to Janeke Wesseling / Vanessa Ohlraun -- Painting in times of research / Gijs Frieling -- Visual contribution / Philippe Van Snick -- The academy and the corporate public / Stephan Dillemuth -- Fleeting profundity / Moniek Toebosch -- And, and, and so on and so forth / WJM Kok -- A blind man sometimes hits the crow / Barbara Visser.
Includes bibliographical references and indexes.
boek